Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s40195-015-0272-2
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Intercritical Heat-affected Zone of X80 Pipeline Steel in Simulated In-Service Welding

Abstract: The intercritical heat-affected zone (ICHAZ) of X80 pipeline steel was simulated by using the Gleeble-3500 thermal/mechanical simulator according to the thermal cycle of in-service welding. The microstructures of ICHAZ with different cooling rates were examined, and the hardness, the toughness and corresponding fractography were investigated. Results show that untransformed bainite and ferrite as well as retransformed fine bainite and martensite-austenite (M-A) constituents constitute the microstructure of ICH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…This subregion needs more attention to be known as the local brittle zone [5,8] (LBZ). The temperature range between A c1 and A c3 , is favorable to MA microconstituent formation in multipass weldments [2,5,8], as it can deteriorate the steel toughness, depending on its size and distribution in the ferritic matrix [9,10]. The following sub-region is reheated in the subcritical temperature range: it arises the SC-CGHAZ.…”
Section: Introductionmentioning
confidence: 99%
“…This subregion needs more attention to be known as the local brittle zone [5,8] (LBZ). The temperature range between A c1 and A c3 , is favorable to MA microconstituent formation in multipass weldments [2,5,8], as it can deteriorate the steel toughness, depending on its size and distribution in the ferritic matrix [9,10]. The following sub-region is reheated in the subcritical temperature range: it arises the SC-CGHAZ.…”
Section: Introductionmentioning
confidence: 99%
“…The Multiphysics Object-Oriented Simulation Environment (MOOSE), which is an open-source finite-element analysis software framework developed and maintained by Idaho National Laboratory, was used for the X100 pipeline steel laser-welding temperature field simulation. To compare the laser-welding temperature field simulation results with the actual working conditions of the welding process, a two-dimensional finite-element model consistent with the actual welding joint size was established through reasonable model abstraction and reliable data for the material thermophysical parameters that were calculated by JmatPro [31][32][33][34][35]. The material thermophysical parameters are shown in Table 3.…”
Section: Establishment and Solution Of The Finite-element Modelmentioning
confidence: 99%
“…According to the shape parameters of the weld seam and the welding heat-affected zone (HAZ), the heat-source model for a Gaussian-distributed rotating body is proposed (Equations (1)-(3)). Heat convection, heat conduction, and heat radiation are taken into account in the boundary conditions (Equations 4and 5) [32,34,[36][37][38][39][40]. The model was solved by the Preconditioned Jacobian-Free Newton-Krylov algorithm (PJFNK).…”
Section: Establishment and Solution Of The Finite-element Modelmentioning
confidence: 99%
“…Considering the effect of effective grain size on the toughness, it is suggested that both M-A constitutions and effective grain size are the key factors to determine the absorbed energy when t 8/5 is larger than 60 s. However, at high heat input, M-A constitutions plays more dominant role on the toughness than effective grain size owing to severe damage of M-A constitutions on the toughness. 3,[26][27][28][29][30][31] Coarse austenite grain size increases the size of M-A constituents and lowers the CGHAZ impact energy. Li et al 26) have elucidated the role of the fraction, size, shape, distribution of M-A constituents on impact toughness and concluded that the size of M-A constituent was influenced by the prior austenite grain size, consequently, which governed impact energy.…”
Section: M-a Constitutionsmentioning
confidence: 99%